Verification of Nuclear Magnetic Resonance Characterization of Traditional Homeopathically Manufactured Metal (Cuprum metallicum) and Plant (Gelsemium sempervirens) Medicines and Controls - Van Wassenhoven, Michel; Goyens, Martine; Henry, Marc; Cumps, Jean; Devos, Philippe (Homeopathy, 2020)
Background Nuclear magnetic resonance (NMR) proton relaxation is sensitive to the dynamics of the water molecule, H2O, through the interaction of the spin of the proton (1H) with external magnetic and electromagnetic fields. NMR relaxation times describe how quickly the spin of 1H, forced in a direction by an external electromagnetic field, returns to a normal resting position. As a result, such measurements allow us potentially to describe higher structuring of water in homeopathic medicines.Objective The purpose of the present study was to verify whether specific NMR relaxation times could be measured in full lines of cH dynamizations of a metal (copper) and of a plant substance (Gelsemium sempervirens), compared with a solvent control, a potentized lactose control and a control prepared by simple dilution, in three production lines. It is aimed at verification of a previous publication (2017) on two new manufacturing lines of the same starting material and controls.Materials and Methods To monitor dilution and potentization processes, measurements of 1H spin-lattice T1 and spin-spin T2 relaxation times were used. T1 and T2 relaxation times were measured at 25°C with a spin analyser working at a frequency of 20 MHz. To account for its possible role as a confounding factor, free oxygen was also measured in all samples, using a MicroOptode meter.Results When the values of the three production lines were pooled, a statistically significant discrimination of NMR relaxation times between the medicines and their controls was confirmed. We found for copper cH and Gelsemium sempervirens cH a highly significant influence of the starting material (p = 0.008), a highly significant influence of level of dilution (p < 0.001), and a significant influence of the O2 concentration (p = 0.04).Conclusions We have evidence of an obvious retention of a specific magnetic resonance signal when a substance (lactose, copper, Gelsemium) is diluted/potentized in pure water. This means that homeopathic solutions cannot be considered to be pure water. O2 is a covariant and not an explanatory variable: this factor itself is too weak to explain the NMR signal specificities in potentized samples. Homeopathic dilutions may thus have a specific material configuration governed not only by the potentized substance but also by the chemical nature of the containers, the chemical nature of dissolved gases and even by the electromagnetic environment. This sensitivity of homeopathically prepared medicines to electromagnetic fields may be amplified by the processes routinely applied during their preparation; because it occurs only when a dynamization has been performed, we may call this phenomenon “dynamic pharmacy”.
Keywords: nuclear magnetic resonance relaxation times; copper; Cuprum metallicum; Gelsemium sempervirens; water; homeopathy; potentization; dynamization; dynamic pharmacy; verification; confirmation